2006
DOI: 10.2486/indhealth.44.433
|View full text |Cite
|
Sign up to set email alerts
|

Heat Stress of Helicopter Aircrew Wearing Immersion Suit

Abstract: The objectives of the present study were to define the lowest ambient air and cabin temperatures at which aircrews wearing immersion protection are starting to experience thermal discomfort and heat stress during flight operations, and to characterize during a flight simulation in laboratory, the severity of the heat stress during exposure to a typical northern summer ambient condition (25°C, 40% RH). Twenty male helicopter aircrews wearing immersion suits (insulation of 2.2 Clo in air) performed 26 flights wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 11 publications
0
11
0
Order By: Relevance
“…Thermal comfort in helicopter aircrew wearing immersion suits seemed to show an anecdotal positive trend with ambient temperature, cabin temperature, and the cabin wet-bulb globe temperature index. 18 Thermal sensation during exercise in cool and cold water is suggested to be moderately correlated with skin temperature and rectal temperature. …”
Section: Perceptual Heat Strain Indicesmentioning
confidence: 99%
“…Thermal comfort in helicopter aircrew wearing immersion suits seemed to show an anecdotal positive trend with ambient temperature, cabin temperature, and the cabin wet-bulb globe temperature index. 18 Thermal sensation during exercise in cool and cold water is suggested to be moderately correlated with skin temperature and rectal temperature. …”
Section: Perceptual Heat Strain Indicesmentioning
confidence: 99%
“…The very nature of being impermeable contributed to the bad ventilation of immersion suits. As it was concluded by several research studies, the relatively high thermal resistance and extremely low water vapor permeability of clothing ensemble impede evaporative heat dissipation and thus elevate the rate of heat storage, creating a state of uncompensable heat stress [32][33][34].…”
Section: Heat Stress Issue Associated With Immersion Suitsmentioning
confidence: 99%
“…Human trials were conducted in a climatic chamber at Defense Research and Development Canada to study the heat stress of the aircrews when carrying on a certain level of activity. The severity of heat stress was investigated during the flights of aircrew in a temperature range between À15 C and 25 C. It was concluded that during the summer in northern climates, aircrews wearing immersion suits might experience thermal discomfort and heat stress at ambient or cabin air temperature as low as 18 C [32]. One of the reasons that resulted in thermal discomfort is the impermeability of certain immersion suits.…”
Section: Heat Stress Issue Associated With Immersion Suitsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thermal comfort in helicopter aircrew wearing immersion suits seemed to show an anecdotal positive trend with ambient temperature, cabin temperature, and the cabin wet-bulb globe temperature index. 18 Thermal sensation during exercise in cool and cold water is suggested to be moderately correlated with skin temperature and rectal temperature. 72…”
Section: Perceptual Heat Strain Indicesmentioning
confidence: 99%